Characterization of Minerals, Metals, and Materials 2019 - Li, Bowen; Li, Jian; Ikhmayies, Shadia; Zhang, Mingming; Kalay, Yunus Eren; Carpenter, John S.; Hwang, Jiann-Yang; Monteiro, Sergio Neves; Bai, Chenguang; Escobedo-Diaz, Juan P.; Spena, Pasquale Russo; Goswami, Ramasis (The Minerals, Metals & Materials Series, 2019)
This volume is focused on the advancements of characterization of various minerals, metals, and materials from bulk scale to nanoscale, and on the applications of characterization results on the processing of these materials. Topics include extraction and processing of various minerals, and the process-structure-property relationship of metal alloys, glasses and ceramics, polymers, composites, and carbon used as functional and structural materials. Advanced methodology and instrumentation for materials characterization are emphasized. The collection provides up-to-date achievements on many types of materials for the scientists and engineers engaged in research, development, and production. .